Analisis Pengalokasian Dana Desa Sebelum dan Selama Covid-19 di Desa Pakamban Daya Kec. Pragaan Kab. Sumenep Tahun 2019-2021 - Aprilia, Firda Alfaini; Ervina, Deasy (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The allocation of village funds is the determination of the amount of money or costs or funds sourced from the APBN which is intended to create village independence by carrying out development, coaching and community empowerment. In this right, the financial management cycle is also important, starting from planning, implementation, administration, reporting and accountability. This study aims to analyze the financial management cycle of village funds and analyze the budget and realization of village fund allocations before and during covid-19 in Pakamban Daya village, Pragaan sub-district, Sumenep district. This type of research method uses descriptive qualitative. The information used in this research is documentation and interviews after which it will be described to make it easier for readers to understand the research. The results of this study indicate that Pakamban Daya village has implemented the village fund financial management cycle correctly, starting from planning, implementation, administration, reporting and accountability. The budget and realization of village fund allocations have been inconsistent which has led to the detection of Covid-19 cases since 2020.